1991
DOI: 10.1017/s0081305200018197
|View full text |Cite
|
Sign up to set email alerts
|

Feeder Cattle Price Differentials in Georgia Teleauctions

Abstract: Three Georgia feeder cattle teleauction markets were analyzed from 1977 to 1988 to estimate the impacts of cattle characteristics and market conditions on prices. Cattle characteristic price impacts were similar to those in previous studies. The impact of feeder cattle futures price on teleauction price was positive but varied across markets. Optimal lot size ranged from 143 to 276 head. In one market, 14 lots were necessary to generate positive price impacts. Additional buyers were estimated to have a $.30/cw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
4
12
0
Order By: Relevance
“…Most of the results presentcd in Table 2 are consistent with previous research on fecder cattle price determination Lambert et al;Turner et al;Buccola 1982). Lighter weight (<600 lbs) steers were associatcd with higher prices across all three telcauctions.…”
Section: Lot Characteristics and Market Forcessupporting
confidence: 90%
See 2 more Smart Citations
“…Most of the results presentcd in Table 2 are consistent with previous research on fecder cattle price determination Lambert et al;Turner et al;Buccola 1982). Lighter weight (<600 lbs) steers were associatcd with higher prices across all three telcauctions.…”
Section: Lot Characteristics and Market Forcessupporting
confidence: 90%
“…Theteleauctionorganization that transferred the least amount of information about the cattle had the greatest number of reputation sellers while the organization with the most information about sellers' cattle given to buyers registered no significant seller reputations. Reputations can help buyers estimate quality in the absence of complete information.Most research identifying significant factors influencing feeder cattle prices has focused on cattle and market characteristics (Buccola, 1980(Buccola, , 1982Schroeder et al;Lambert et al;Turner et al;Bailey et al). These studies have investigated price determination in traditional, telephone, and video auctions and explained much of the variation in feeder cattle price.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lower the initial body weight, the more weight the calves could gain for the buyer. 13 Larger-frame calves in the 15-year video study reported here and in other studies [2][3][4][5][7][8][9][10][11]13 have sold at higher prices, compared with prices paid for smallerframe calves, because the growth patterns and finish weight of larger-frame calves are more acceptable to the cattle feeding and meat processing industries. Analysis of the economic factors accounting for the large variations in year-to-year price deductions for heavier calves was beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Analysis of the data for the study reported here revealed that producers have consistently enhanced the market price of their calves by selling crossbred steer calves with a medium or large frame in large lots with uniformity of quality, weight, and breed within the lots. Data from studies [2][3][4][5][8][9][10][11][12][13][14] conducted in Arkansas, Georgia, Oklahoma, and California are in general agreement that cattle markets prefer Angus calves, which typically were sold for higher prices than were calves of other breeds. 1 One noteworthy difference between video auctions and traditional auctions is that optimum lot size is larger at video auctions because of the inability of buyers to pool video auction lots for shipments and their desire to match lot size with that specified by feedlots.…”
Section: Discussionmentioning
confidence: 99%